Vanishing Bile Duct Syndrome in a Patient with Uterine Cancer and Paraneoplastic Systemic Sclerosis. Issue 1 (2018) - Sedhom, Daniel; Herrmann, Amanda; D'Souza, Melroy; Fyfe, Billie; Zaldana, Francisco; Schlesinger, Naomi; Rustgi, Vinod
ABSTRACT : N/A: Vanishing bile duct syndrome (VBDS) is a rare entity of acquired disorders resulting in cholestasis secondary to progressive destruction of intrahepatic bile ducts. The syndrome has been described in the setting of autoimmune disorders, medication toxicities, genetic disorders, infectious etiologies, and in rare cases, neoplastic processes. There are no known case reports of VBDS in the setting of uterine malignancy. We present a case of VBDS in a patient with underlying uterine cancer complicated by paraneoplastic systemic sclerosis.